Effects of social housing on alcohol intake in mice depend on the non-social environment - Johnson, Michael C.; Zweig, Jonathan A.; Zhang, Yangmiao; Ryabinin, Andrey E. (Frontiers in Behavioral Neuroscience, 2024)
Background. Excessive alcohol consumption leads to serious health problems. Mechanisms regulating alcohol drinking are insufficiently understood. Previous preclinical studies suggested that non-social environmental and social environmental complexity can regulate alcohol consumption in opposite directions. However, previous studies did not include all conditions and/or did not include female rodents. Therefore, here we examined the effects of social versus single housing in standard versus non-standard housing conditions in male and female mice. Methods. Adult C57BL/6J mice were housed in either standard shoebox cages or in automated Herdsman 2 (HM2) cages and exposed to a two-bottle choice procedure with 3% or 6% ethanol versus water for five days. The HM2 cages use radiotracking devices to measure fluid consumption of individual mice in an undisturbed and automated manner. In both housing conditions, mice were housed either at one or at four per cage. Results. In standard cages, group housing of animals decreased alcohol consumption and water consumption. In HM2 cages, group housing significantly increased ethanol preference and decreased water intake. There were no significant differences in these effects between male and female animals. These observations were similar for 3% and 6% ethanol solutions but were more pronounced for the latter. The effects of social environment on ethanol preference in HM2 cages were accompanied by an increase in the number of approaches to the ethanol solution and a decrease in the number of approaches to water. The differences in ethanol intake could not be explained by differences in locomotor or exploratory activity as socially housed mice showed less non-consummatory visits to the ethanol solutions than single-housed animals. In addition, we observed that significant changes in behaviors measuring the approach to the fluid were not always accompanied by significant changes in fluid consumption, and vice versa, suggesting that it is important to assess both measures of motivation to consume alcohol. Conclusions. Our results indicate that the direction of effects of social environment on alcohol intake in mice depend on the non-social housing environment. Understanding mechanisms by which social and non-social housing conditions modulate alcohol intake could suggest approaches to counteract environmental factors enhancing hazardous alcohol consumption.